Percepción del sobrepeso infantil en familias de la urbanización aranjuez - Medina Hoyos, Imelda Victoria (2017)
Explorative descriptive research in order to determine the perception of childhood overweight and the prevention actions that families who come at Aranjuez Health Center in the district of Trujillo, Trujillo Province, department of La Libertad (Peru) have. A survey was applied to the families of children diagnosed as being overweight, which are treated at the Aranjuez health center. The GESTALT (2008) gives theoretical support about perception, the World Health Organization (WHO) about overweight and prevention, and the concept of Family is extracted from Bustamante (2004). The findings of the study reported that Aranjuez families mostly have a correct perception of their children's overweight, it is noteworthy that children under 5 years of age have limited physical activity, when at that age is gaming the most important which allows their comprehensive development. Furthermore, it was found that families recognize some prevention actions for childhood overweight, but have difficulty applying them. On the other hand, the long time on television, can bring damage to the sight and is a problem that at the moment we are not addressing. That is why guidelines are drawn up to address interventions in family health and in particular the prevention of overweight in children.